Generic Cancellable Note Analytics - Tim Xiao (ZBW - Leibniz Information Centre for Economics, 2022)
Many financial derivative products have cancellation provision. They usually have a regular leg and a cancellation leg. The cancellation leg can cancel the regular leg when a cancellation event occurs. This paper presents a generic model for pricing cancellable derivatives. It computes the cancellation probability, fair value, and risk of a cancellable note.
Keywords: 330; cancellable note; derivative valuation